Kerosene as an alternative to xylene in histopathological tissue processing and staining: An experimental study - Janardhanam Dineshshankar; Manikandan Saranya; Periyasamy Tamilthangam; Jeyaraman Swathiraman; Kumaravel Shanmathee; Ravichandran Preethi (Wolters Kluwer Medknow Publications, 2019)
Background: Conventional tissue processing is as old as 100 years and still remains the gold standard. Tissue processing involves many steps, of which one of the important steps is clearing. Xylene is one of the common clearing agents used in laboratory, but it is carcinogenic and teratogenic. Aim: The aim of this study was to substitute conventionally used xylene with kerosene in tissue processing and staining. Materials and Methods: Thirty bits of chicken tissue samples were collected; each was randomly separated into two groups: tissue processing and staining. Instead of conventional xylene, we used kerosene. The tissue blocks were subjected to sectioning and staining, and finally, they were observed under light microscope. Results: Tissue samples that were processed and cleared with kerosene showed equal clearing and staining without any alterations of the tissue morphology and cellular details with that of xylene. Conclusion: Kerosene can be used as a substitute to xylene without posing any health risk or compromising the cellular integrity.